PENGARUH KEAMANAN, KEMUDAHAN PENGGUNAAN, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS LAZADA - Yuli Sudarwanto; Ambar Lukitaningsih; Bernedetta Diansepti Maharani (Jurnal Bina Bangsa Ekonomika, 2021)
This research aims to determine the effect of security, ease and trust on online purchasing decisions on the Lazada.co.id sites. The population used in this study is students of the Faculty of Economics UST.  This type of research is quantitative research  explanatory method. While the sampling technique uses purposive sampling with the number of samples obtained from the slovin formula as many as 100 respondents. While the sampling technique uses purposive sampling with the number of samples obtained from the slovin formula as many as 100 respondents. The method used in the collection of research data is koesiuner which is interval with 5 (five) Linkert scales. The analytical techniques used in this study are multiple linear regressions assisted by spss software application 2016. The results showed that partially and simultaneously variable security, ease of use and trust had a positive and significant effect on purchasing decisions on the Lazada site